INVESTIGATION THE LEADERSHIP STYLE AND PERSONALITY TRAITS AFFECT WORK PERFORMANCE IN THE DIGITAL TRANSFORMATION ERA-TAKING TAIWAN LIFE INSURANCE COMPANY AS AN EXAMPLE - Pan, Yi-Chia; Li, Cheng-Lung (International Journal of Application on Economics and Business, 2025)
Financial and insurance industry executives face the financial digital transformation environment and the emergence of new people in the post-zero (born after 2000) society. Will their mentality changes due to changes in their own personality traits and management experience in developing organizations and performance impact? The present study focuses on how the personality traits of financial and insurance industry executives and the leadership style they present in the face of environmental evolution affect individual and group performance. Through qualitative research methods, in-depth interviews, actual participation. The design was based on physical evidence, and the data was collected after one-on-one in-depth interviews with eight senior managers and personal observation. The research results and suggestions are helpful in terms of personality traits and leadership styles in the digital transformation environment, the homogeneity and differences in supervisor leadership styles in the digital transformation environment, and the asymmetry of resources and equipment and performance differences in the digital transformation of the financial and insurance industry caused by the urban-rural gap. In the life insurance industry, we promote business and develop organizations to achieve sustainable operations.